2015
DOI: 10.1371/journal.pone.0137074
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Unfolding Properties of Chd64, a Small, Single Domain Protein with a Globular Core and Disordered Tails

Abstract: Two major lipophilic hormones, 20-hydroxyecdysone (20E) and juvenile hormone (JH), govern insect development and growth. While the mode of action of 20E is well understood, some understanding of JH-dependent signalling has been attained only in the past few years, and the crosstalk of the two hormonal pathways remains unknown. Two proteins, the calponin-like Chd64 and immunophilin FKBP39 proteins, have recently been found to play pivotal roles in the formation of dynamic, multiprotein complex that cross-links … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…While the cytoplasmic localization of Chd64 could be linked with its putative role in the modulation of actin cytoskeleton, its nuclear presence fits with previous studies reporting binding of Chd64 on Juvenile hormone receptor element 1 (JHRE1) and ecdysone response element (EcRE) ( Li et al, 2007 ), suggesting a putative role of Chd64 in transcription modulation. Interestingly, structural analysis indicated that Chd64 is a pliable protein-containing terminal intrinsically disordered regions (IDRs) that facilitate multiple molecular interactions ( Kozłowska et al, 2014 ; Tarczewska et al, 2015 ). Our data clearly demonstrate a complete absence of Chd64 expression in muscles during fly development.…”
Section: Discussionmentioning
confidence: 99%
“…While the cytoplasmic localization of Chd64 could be linked with its putative role in the modulation of actin cytoskeleton, its nuclear presence fits with previous studies reporting binding of Chd64 on Juvenile hormone receptor element 1 (JHRE1) and ecdysone response element (EcRE) ( Li et al, 2007 ), suggesting a putative role of Chd64 in transcription modulation. Interestingly, structural analysis indicated that Chd64 is a pliable protein-containing terminal intrinsically disordered regions (IDRs) that facilitate multiple molecular interactions ( Kozłowska et al, 2014 ; Tarczewska et al, 2015 ). Our data clearly demonstrate a complete absence of Chd64 expression in muscles during fly development.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of replicate trees in which the associated taxa clustered together in the bootstrap test (1,000 replicates) are shown next to the branches. Tarczewska et al, 2015). To date, the hJHBP has only been identified and functionally tested in some lepidopterans (Orth et al, 2003;Suzuki et al, 2011), which was used to deliver the juvenile hormone to target tissue and protect it from degradation (Hidayat and Goodman, 1994;Debski et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Analytical SEC was performed as described previously60. Briefly, a Superdex 200 10/300 GL column was equilibrated with buffer C and calibrated using a set of standard proteins60.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, a Superdex 200 10/300 GL column was equilibrated with buffer C and calibrated using a set of standard proteins60. The column volume (V t ) was 24 ml, and the column void volume (V 0 ) was determined to be 7.86 ml using blue dextran.…”
Section: Methodsmentioning
confidence: 99%